ECONOMIC FEASIBILITY OF CRAFT BEER PRODUCTION - BLACK BEER - Valencia Delascrea, Cesar Renan; Yada de Almeida, Macela Midore (Revista Interface Tecnológica, 2021)
This article aims to expose the power that the brazilian beer marketing has to Other nations. Along with this, it will aim to demonstrate the trend of consumers in relation to products from homemade formulas, bringing innovation, markentig opportunity and differentiated flavor in the face of competion. With this, a business idea will be presented, which aims to meet an expressive demand from craft beer lovers, were inserted and addressed all parameters that the market needs and requires, from financial analysis and marketing to become viable in the eyes of inventors and especially consumers.
Keywords: Economic viability; craft beer